Factors associated with increased mortality in a predominantly HIV-infected population with Stevens Johnson syndrome and toxic epidermal necrolysis. - Lauren Knight; Rudzani Muloiwa; Sipho Dlamini; Rannakoe J Lehloenya (PLoS ONE, 2014)
Introduction Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are life-threatening drug reactions with a higher incidence in HIV-infected persons. SJS/TEN are associated with skin and mucosal failure, predisposing to systemic bacterial infection (BSI), a major cause of death. There are limited data on risk factors associated with BSI and and mortality in HIV-infected people with SJS/TEN. Methods We conducted a retrospective study of patients admitted to a university hospital with SJS/TEN over a 3 year period. We evaluated their underlying illnesses, eliciting drugs, predictive value of bacterial skin cultures and other factors associated with mortality and BSI in a predominantly HIV-infected population by comparing characteristics of the patients who demised and those who survived. Results We admitted 86 cases during the study period and 67/86(78%) were HIV-infected. Tuberculosis was the commonest co-morbidity, diagnosed in 12/86(14%) cases. Skin cultures correlated with BSI by the same organism in 7/64(11%) cases and 6/7 were Gram-negative. Two of the 8 cases of Gram-negative BSI had an associated Gram-negative skin culture, although not always the same organism. All 8 fatalities had >30% epidermal detachment, 7 were HIV-infected, 6 died of BSI and 6 had tuberculosis. Conclusions Having >30% epidermal detachment in SJS/TEN carries an increased risk of BSI and mortality. Tuberculosis and BSI are associated with higher risk of death in SJS/TEN. Our data suggests there may be an association between Gram-negative BSI and Gram-negative skin infection.